Novel plant-derived exosome-like nanovesicles from Catharanthus roseus: preparation, characterization, and immunostimulatory effect via TNF-α/NF-κB/PU.1 axis - Xiaozheng Ou; Haoran Wang; Huilin Tie; Jiapei Liao; Yuanyuan Luo; Weijuan Huang; Rongmin Yu; Liyan Song; Jianhua Zhu (Journal of Nanobiotechnology, 2023)
Abstract Background Plant-derived exosomes-like nanovesicles (PDENs) have been found to be advantageous in disease treatment and drug delivery, but research on their biogenesis, compositional analysis, and key marker proteins is still in its infancy, which limits the standardized production of PDENs. Efficient preparation of PDENs continues to be a major challenge. Results Novel PDENs-based chemotherapeutic immune modulators, Catharanthus roseus (L.) Don leaves-derived exosome-like nanovesicles (CLDENs) were isolated from apoplastic fluid. CLDENs were membrane structured vesicles with a particle size of 75.51 ± 10.19 nm and a surface charge of −21.8 mV. CLDENs exhibited excellent stability, tolerating multiple enzymatic digestions, resisting extreme pH environments, and remaining stable in the gastrointestinal simulating fluid. Biodistribution experiments showed that CLDENs could be internalized by immune cells, and targeted at immune organs after intraperitoneal injection. The lipidomic analysis revealed CLDENs’ special lipid composition, which contained 36.5% ether-phospholipids. Differential proteomics supported the origin of CLDENs in multivesicular bodies, and six marker proteins of CLDENs were identified for the first time. 60 ~ 240 μg/ml of CLDENs promoted the polarization and phagocytosis of macrophages as well as lymphocyte proliferation in vitro. Administration of 20 mg/kg and 60 mg/kg of CLDENs alleviated white blood cell reduction and bone marrow cell cycle arrest in immunosuppressive mice induced by cyclophosphamide. CLDENs strongly stimulated the secretion of TNF-α, activated NF-κB signal pathway and increased the expression of the hematopoietic function-related transcription factor PU.1 both in vitro and in vivo. To ensure a steady supply of CLDENs, plant cell culture systems of C. roseus were established to provide CLDENs-like nanovesicles which had similar physical properties and biological activities. Gram-level nanovesicles were successfully obtained from the culture medium, and the yield was three times as high as the original. Conclusions Our research supports the use of CLDENs as a nano-biomaterial with excellent stability and biocompatibility, and for post-chemotherapy immune adjuvant therapy applications. Graphical Abstract